2017
DOI: 10.1038/srep40144
|View full text |Cite
|
Sign up to set email alerts
|

Predictive screening of M1 and M2 macrophages reveals the immunomodulatory effectiveness of post spinal cord injury azithromycin treatment

Abstract: Spinal cord injury (SCI) triggers a heterogeneous macrophage response that when experimentally polarized toward alternative forms of activation (M2 macrophages) promotes tissue and functional recovery. There are limited pharmacological therapies that can drive this reparative inflammatory state. In the current study, we used in vitro systems to comprehensively defined markers of macrophages with known pathological (M1) and reparative (M2) properties in SCI. We then used these markers to objectively define the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
131
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 124 publications
(140 citation statements)
references
References 46 publications
9
131
0
Order By: Relevance
“…Azithromycin and other macrolide antibiotics are now being tested as immunomodulatory agents for CNS disorders. Specifically, we and others observed immunomodulatory effects and improved recovery with AZM treatment in spinal cord injury, stroke, and retinal ischemia/reperfusion injury . The neuroprotective properties of AZM in these models are associated with direct effects on macrophages .…”
Section: Introductionmentioning
confidence: 55%
“…Azithromycin and other macrolide antibiotics are now being tested as immunomodulatory agents for CNS disorders. Specifically, we and others observed immunomodulatory effects and improved recovery with AZM treatment in spinal cord injury, stroke, and retinal ischemia/reperfusion injury . The neuroprotective properties of AZM in these models are associated with direct effects on macrophages .…”
Section: Introductionmentioning
confidence: 55%
“…Furthermore, inhibition of the IRE1 pathway through treatment with STF‐080310 prevented ER expansion and suppressed the M2 macrophage phenotype. This was observed in vitro through assessment of CD206 and arginase‐1, two strong markers used to characterize M2‐macrophage expression . Combined, the data presented suggest that therapeutic targeting of the IRE1 pathway or IL‐6 signaling may prevent the profibrotic activity of M2‐like macrophages in vivo .…”
Section: Introductionmentioning
confidence: 58%
“…Thus, it is likely that MARCO can bind myelin lipids effectively. Although it has not been identified as a myelin receptor in SCI, we recently observed that macrophages upregulate MARCO in response to proinflammatory stimuli and express MARCO in the injured spinal cord (Gensel, Kopper, Zhang, Orr, & Bailey, ; Orr et al, ). MARCO activation, therefore, may be a potential mechanism for proinflammatory macrophage‐mediated myelin removal in SCI.…”
Section: Macrophage Receptor–mediated Myelin Removalmentioning
confidence: 99%
“…Similarly, it is well documented that macrophages increase IL‐12 release with myelin stimulation (Sun et al, ; Wang et al, ). Given that MARCO is present on macrophages after SCI (Gensel et al, ), it is possible that MARCO‐mediated myelin clearance may influence the M1‐like polarization observed in SCI. Conversely, SRAI/II has been implicated in the inhibition of IL‐12 production (Józefowski et al, ; Józefowski & Kobzik, ).…”
Section: Myelin–macrophage Interactionsmentioning
confidence: 99%